Evaluating the effectiveness of a character education program in a junior high school: a CIPP model approach - Ni Putu Eka Trisdayanti; Basilius Redan Werang; Kadek Rihendra Dantes (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2025)
The study employed a descriptive quantitative design involving 40 respondents consisting of teachers, the principal, and administrative staff selected through purposive sampling based on their direct involvement in program implementation. Data were collected using a structured questionnaire based on a five-point Likert scale (1 = strongly disagree to 5 = strongly agree). The instrument was developed according to CIPP indicators and tested for validity using product-moment correlation, with all items meeting the minimum validity criteria (r > 0.30). Reliability testing using Cronbach’s Alpha showed a coefficient of 0.87, indicating high internal consistency. Data analysis was conducted using descriptive statistics (mean and standard deviation) and T-score transformation to determine the effectiveness category of each component. The results show that the Context component obtained a mean score of 3.98 (SD = 0.54), indicating that the program foundation, including policy support and cultural alignment, is well established. The Input component achieved a mean of 3.76 (SD = 0.61), suggesting that human resources and facilities are generally adequate, although several aspects require strengthening. The Process component recorded a mean score of 3.72 (SD = 0.58), reflecting relatively consistent implementation, with improvements needed in monitoring and supervision. Meanwhile, the Product component obtained a mean of 4.02 (SD = 0.49), indicating positive outcomes in students’ character development. Based on the overall average score (M = 3.87; SD = 0.55), the Character Education Program can be categorized as effective according to predetermined effectiveness criteria (mean score ≥ 3.50). However, enhancement of program inputs, particularly in technical support and resource optimization, is recommended to ensure long-term sustainability and improved program outcomes.